Isolated Central Nervous System Circuits - Ballanyi, Klaus; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Advances in methodologies and experimental models are pivotal to furthering our understanding of central nervous system (CNS) functions in mammals. Isolated Central Nervous System Circuits examines the application a variety of technologies to mostly active in vitro preparations from basically different CNS regions with a diversity of functions.  From patch-clamp, multiphoton imaging, live fluorescent protein expression, or immunohistochemistry techniques to acute or 'organotypic' slices and en bloc preparations, this detailed volume features key protocols and examples for exciting results from the labs of renowned experts.  Written for the popular Neuromethods series, chapters include the kind of thorough implementation advice that is vital for achieving successful results.   Comprehensive and cutting-edge, Isolated Central Nervous System Circuits will greatly aid scientists to further improve models and to develop corresponding models of not yet intensively studied structures such as nucleus ruber, superior colliculus, or basal ganglia.
Autonomic Nervous System In Vitro: Studying Tonically Active Neurons Controlling Vagal Outflow in Rodent Brainstem Slices -- Anatomically ‘Calibrated’ Isolated Respiratory Networks from Newborn Rodents -- Physiological Properties of Human Fetal Cortex In Vitro -- Histological Characterization of Physiologically Determined Fast-Spiking Interneurons in Slices of Primate Dorsolateral Prefrontal Cortex -- Neural Circuits Underlying Circadian Oscillations in Mammals: Clocks in a Dish -- Osmoregulatory Circuits in Slices and En Bloc Preparations of Rodent Hypothalamus -- Establishing In Vivo-Like Activity in Rat Cerebellar Cells Maintained In Vitro -- Spontaneous Rhythmic Activity in the Adult Cerebral Cortex In Vitro -- Living Human Brain Slices: Network Analysis Using Voltage Sensitive Dyes -- Intact In Vitro Preparations of the Neonatal Rodent Cortex: Analysis of Cellular Properties and Network Activity -- Spontaneous Neural Network Oscillations in Hippocampus, Cortex, and Locus Coeruleus of Newborn Rat and Piglet Brain Slices -- Neuronal Networks in the In Vitro Isolated Guinea Pig Brain -- The Study of Respiratory Chemoreflexes Using a Novel Dual-Perfused Rodent Preparation -- Defined Medium Organotypic Cultures of Spinal Cord Put ‘Pain in a Dish’ -- Rodent Isolated Spinal Cord Preparations to Examine Motor Output.
Keywords: Neurosciences; Human physiology; Neurosciences; Human Physiology